Process Approach in Multi-Agent Systems - Stanek, Stanisław; Żytniewski, Mariusz (Podejście procesowe do systemów wieloagentowych, 2010)
One of the challenges that developers have to face when building multi-agent systems involves the design of a system architecture that would support seamless coordination of the activities of multiple agents. Despite a rich variety of technologies, design methodologies and internal agent architectures, the goal- and task-orientation of the components remains a common feature of all multi-agent systems. Concerted actions performed by specific constituents can be, whatever architecture is adopted, regarded as a business process whose actors are people, information systems and software agents. The aim of the paper is to demonstrate the possibilities of applying the business approach in developing multi-agent systems, with a focus on employing the WADE system that represents an extension of the JADE platform.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2010; Nr 147, s. 255-266
Keywords: multi-agent systems; process approach; workflow; JADE; WADE